(untitled) - Rajan, Claire (Australia; Boston, Mass., 2007)
Oracle 10g Database Administrator II: Backup/Recovery uses the most current database release from Oracle to provide thorough coverage of an Oracle database through the day-to-day duties of a database administrator. This text drills down key tools and techniques for Oracle database backup, recovery and network administration and provides good preparation for the update Oracle certification exam, Database Fundamentals I (#1Z0-043). In addition to extensive review material, the end of chapter content also includes comprehensive coverage of the exam objectives and exam-like practice questions. This text is the perfect compliment to the Oracle 10g: Database Administrator: Implementation and Administration (DBA1) text and the 1Z0-042
Keywords: Data recovery (Computer science),Database management,Phục hồi dữ liệu (khoa học máy tính),Quản trị cơ sỡ dữ liệu